The Skills Balancing Act in Sub-Saharan Africa : Investing in Skills for Productivity, Inclusivity, and Adaptability. - Arias, Omar (Africa Development Forum Ser., 2018)
Despite strong recent economic growth, Sub-Saharan Africa has levels of economictransformation, poverty reduction, and skill development far below those of other regions. Smart investments in developing skills - aligned with the policy goals of productivity growth, inclusion, and adaptability - can help to accelerate the region's economic transformation inthe 21st century. Sub-Saharan Africa's growing working-age population presents a major opportunity toincrease shared prosperity. Countries in the region have invested heavily in building skills; public expenditure on education increased sevenfold over the past 30 years, and more childrenare in school today than ever before. Yet, systems for building skills in this population havefallen short, and these shortcomings significantly impede economic prospects. In half of thecountries, fewer than two in every three children complete primary school; even fewer reachand complete higher levels of education. Learning outcomes have been persistently poor, leading to substantial gaps in basic cognitive skills - literacy and numeracy - among children, young people, and adults. The literacy rate of the adult population is below 50 percent in manycountries; functional literacy and numeracy rates are even lower. Systemwide change is required to achieve significant progress. Multiple agencies at thecentral and local levels are involved in skills development strategies, making skills "everyone's problem but no one's responsibility." Policies and reforms need to build capacity for evidence-based policies and create incentives to align the behaviors of all stakeholders with the pursuitof national skills development goals. The Skills Balancing Act in Sub-Saharan Africa: Investing in Skills for Productivity, Inclusivity, and Adaptability lays out evidence to inform the policy choices that countries will make in skillinvestments. Each chapter addresses a set of specific questions, drawing on original analysisand synthesis of existing studies to explore key areas: How the skills appropriate to each stage of the life cycle are acquired and what market and institutional failures affect skills formation What systems are needed for individuals to access these skills, including family investments, private sector institutions, schools, and other public programs How those systems can be strengthened How the most vulnerable individuals-those who fall outside the standard systemsand have missed critical building blocks in skills acquisition-can be supported. Countries will face trade-offs - often stark ones - that will have distributional impactsand a bearing on their development path. Committed leaders, reform coalitions, and well-coordinated policies are essential for taking on the skills balancing act in Sub-Saharan Africa.